2013
DOI: 10.1158/1535-7163.mct-12-0895
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells Enhance Prostate Cancer Metastasis via IL-6→Androgen Receptor→TGF-β→MMP-9 Signals

Abstract: While the potential roles of endothelial cells (ECs) in the microvascules of prostate cancer (PCa) during angiogenesis have been documented, their direct impacts on the PCa metastasis remain unclear. We found that the CD31-positive and CD34-positive ECs are increased in PCa compared to the normal tissues and these ECs cells were decreased upon castration, gradually recovered with time, and become increased after PCa progresses into the castration resistant stage, suggesting a potential linkage of these ECs wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 65 publications
(67 reference statements)
4
85
0
Order By: Relevance
“…In prostate cancer, the activation and secretion to the extracellular environment of soluble factors that mediate the cross-talk between tumor cells and tumor stroma, such as interleukins and growth factors, has been reported to play a role in tumor progression (13,14,(38)(39)(40). Our analysis confirm a previously result that demonstrated that Brachyury increases the expression and secretion of TGFb1 in a prostate cell line (13).…”
Section: Discussionsupporting
confidence: 89%
“…In prostate cancer, the activation and secretion to the extracellular environment of soluble factors that mediate the cross-talk between tumor cells and tumor stroma, such as interleukins and growth factors, has been reported to play a role in tumor progression (13,14,(38)(39)(40). Our analysis confirm a previously result that demonstrated that Brachyury increases the expression and secretion of TGFb1 in a prostate cell line (13).…”
Section: Discussionsupporting
confidence: 89%
“…IL-6, a cytokine that can be both pro-and antiinflammatory, plays an important role in the metastasis of prostate cancer (Shariat et al 2002). Endothelial cells have been shown to excrete IL-6 resulting in a decrease in androgen receptor activity leading to increased invasion of the epithelial cells (Wang et al 2013). In HER2 positive breast cancer, IL-6 expression is increased as well (Hartman et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…We recently learned from a study by Wang et al (2013) that endothelial cells within the prostate are increased following ADT. These cells secrete interleukin 6 (IL6), which activates PI3K/AKT signal transduction to suppress AR transactivation (Yang et al 2003).…”
Section: /Cd133mentioning
confidence: 99%